Equitable Science Requires Collegial Debate. Issue 2 (February 2021) - Tiffin, Nicki; Ambler, Jon
Abstract : We welcome an ongoing debate about benefit-sharing related to the use of digital sequence information (DSI) and how to ensure global equity in the use of biological samples, including those donated by human beings.